A STUDY ON THE LEGAL CONSEQUENCES OF ABUSE AND EXCESS OF AUTHORITY IN POLICE APPROACHES IN THE EASTERN REGION OF GOINIA/GO (CIPEEX, 2022)
VIOLENCE IS A PROBLEM THAT HAS PLAGUED BRAZIL FOR DECADES. AMONG THEM IS POLICE VIOLENCE STEMMING FROM ARBITRARY CONDUCT IN APPROACHES THAT OFTEN END UP RESULTING IN DEATH. IN 2021 MORE THAN SIX THOUSAND PEOPLE WERE KILLED BY CIVILIAN AND MILITARY POLICE OFFICERS IN THE COUNTRY, THAT IS, AN AVERAGE OF 17 CIVILIAN DEATHS CAUSED BY POLICE OFFICERS PER DAY IN BRAZIL (USP, 2021). IN VIEW OF THE POSSIBLE UNPREPAREDNESS OF POLICE OFFICERS, A WAVE OF DISTRUST WAS CREATED AMONG THE POPULATION THAT INSTEAD OF FEELING SAFE WITH THE PRESENCE OF THE POLICE, STARTED TO CREATE AVERSION, ACCORDING TO DATA RELEASED BY IPEA (2010), WHERE ¼ OF BRAZILIANS DO NOT TRUST THE CIVIL AND MILITARY POLICE, AND MORE RECENTLY, DATA RELEASED BY DATAFOLHA (2019), 51% OF BRAZILIANS HAVE MORE FEAR THAN TRUST IN THE POLICE FORCES, 41% HAVE MORE TRUST THAN FEAR, AND 2% DO NOT KNOW HOW TO ANSWER. GIVEN THE SUBJECT IN QUESTION, THIS PAPER AIMS TO ANALYZE LAW 13.869/19, CONSIDERED AS THE LAW OF ABUSE OF AUTHORITY, IN VIEW OF THE FACTUAL ASPECTS OF POLICE APPROACH IN THE EASTERN REGION OF GOINIA (BRASIL, 2022). SEEKING TO REACH THE EXPECTED RESULTS, THE WORK WAS DIVIDED INTO STAGES. IN A FIRST MOMENT, IT IS INTENDED TO APPROACH THE LEGALITY OF POLICE APPROACHES, ACCORDING TO THE LEGAL PROVISION AND THE STANDARD OPERATING PROCEDURE (SOP); THEN A FIELD RESEARCH WILL BE DONE, WITH APPLICATION OF QUESTIONNAIRES, IN ORDER TO INVESTIGATE THE PERCEPTION OF THE POPULATION LIVING IN THE EAST REGION OF GOINIA IN RELATION TO POLICE APPROACHES; FINALLY, THE WORK WILL ANALYZE THE LEGAL CONSEQUENCES OF THE ACTS OF ABUSE AND EXCESS OF AUTHORITY IN POLICE APPROACHES, POINTING OUT THE LEGAL MEANS APPLICABLE IN SIMILAR SITUATIONS. THE WORK WILL USE THE QUALI-QUANTITATIVE RESEARCH METHOD, FIELD, DOCUMENTARY, EXPLORATORY, AND EXPLANATORY, SEEKING TO COLLECT AND ANALYZE DATA THAT CAN PROVIDE A FEEDBACK TO SOCIETY. IT IS CONSIDERED IMPORTANT TO DISCUSS THE THEME, FOR THE KNOWLEDGE AND FEASIBILITY OF THE FUNDAMENTAL RIGHTS AND GUARANTEES OF THE CITIZEN ARE NON-NEGOTIABLE AND CONSIDERED DEFENSE INSTRUMENTS TO BE INVOKED IN THE IMMINENCE OR VIOLATION OF RIGHTS. ACCORDING TO PREVIOUS DATA COLLECTED, IT WAS OBSERVED THAT IN THE EASTERN REGION OF GOINIA, THERE ARE MANY COMPLAINTS ABOUT POSSIBLE ABUSES AND EXCESSES OF POWER BY POLICE AUTHORITIES WHEN APPROACHING CITIZENS. HOWEVER, THE POLICE APPROACH SYMBOLIZES AN ADMINISTRATIVE ACT, AND THE LEGALITY OF THE POLICE APPROACH IS REGULATED IN SEVERAL BRANCHES OF BRAZILIAN LAW. FOCUSING ON FUNDAMENTAL RIGHTS AND GUARANTEES AND ON THE DIGNITY OF THE HUMAN PERSON, THE PAPER WILL HIGHLIGHT THE CONSTITUTIONAL ASPECTS OF THE LEGAL CONSEQUENCES OF EXCESS AND ABUSE OF POLICE AUTHORITY WHEN BEING APPROACHED. THUS, FUNDAMENTAL RIGHTS AND GUARANTEES GUIDE POLICE ACTIVITY, AND AS A CONSEQUENCE, THEY ARE THE BASIS FOR A FAIR PERFORMANCE, IN ACCORDANCE WITH THE DIGNITY OF THE HUMAN PERSON AND STRICTLY FOLLOWING WHAT THE LEGISLATION IN FORCE MANDATES.
Keywords: Rights; Society; Violence